CHRONIC ENTEROCOLITIS COMBINED WITH STREPTOZOTOCIN-INDUCED DIABETES IN RATS: MECHANISM OF OXIDATIVE STRESS DEVELOPMENT - Lisnianska, N. V.; Маrushchak M. I.; Antonyshyn, I. V.; Mialiuk, O. P. (International Journal of Medicine and Medical Research, 2017)
Background. Despite numerous studies on chronic inflammatory processes in colon, the complex problem of chronic enterocolitis (CEC) remains relevant. Objective. The aim of the research is to evaluate the lipid peroxide oxidation and antioxidant defence system in rats suffering from chronic enterocolitis development with underlying streptozocine-induced diabetes mellitus. Methods. The study involved 106 white non-linear male rats. Diabetes mellitus (DM) was modeled by a single intraperitoneal administration of streptozotocin to animals (Sigma Aldrich, USA, at a dose of 60 mg/kg of body weight). CEC was induced by a free access of animals to 1.0% solution of carrageenan in drinking water for 1 month. Results. In the wall of small intestine of DM rats, lipid peroxide oxidation increases and the activity of enzyme link of antioxidant defence decreases reliably. The course of experimental CEC in rats is accompanied by the increase in free radical oxidation in the wall of small intestine and simultaneous increase of enzyme activity of antioxidant defence system, compared to the control. In cases of CEC with underlying DM in rats, the development of oxidative stress in the wall of small intestine is caused by the statistically significant increase in levels of diene conjugates and thiobarbituric acid reactive substances, (p<0.01) and the decrease in activity of SOD and catalase. Conclusions. The activation of free radical reactions is an important non-specific mechanism of inflammation development in tissues of small and large intestine in cases of diabetes mellitus.